1992
DOI: 10.1080/00268979200102341
|View full text |Cite
|
Sign up to set email alerts
|

Calculated rovibrational energy levels and infrared spectrum of He-C2H2

Abstract: Accurate calculations of the energies of all bound rovibrational states, of the energies and lifetimes of some metastable states, and of the resulting rovibrational spectrum are performed for the helium-acetylene Van der Waals complex using an iterative secular equation method. The calculations are carried out both on an empirical potential surface which has a single 'T shaped' minimum, and on a potential surface based on ab initio electronic structure calculations which has a single minimum at a linear geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…59. 60, which is essentially exact and has been used in a study of He-C 2 H 2 and in the determination of accurate potential energy surfaces from spectroscopic data for He-CO. 10,11,61 However, the ISE method has never previously been used to simulate hyperfine transitions, and in the He-CO work, 10,11 the partial derivatives of level energies with respect to potential function parameters required by the least-squares procedure were determined by differences, a relatively tedious procedure. The present work therefore uses the "iterative secular equation" ͑ISE͒ method of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…59. 60, which is essentially exact and has been used in a study of He-C 2 H 2 and in the determination of accurate potential energy surfaces from spectroscopic data for He-CO. 10,11,61 However, the ISE method has never previously been used to simulate hyperfine transitions, and in the He-CO work, 10,11 the partial derivatives of level energies with respect to potential function parameters required by the least-squares procedure were determined by differences, a relatively tedious procedure. The present work therefore uses the "iterative secular equation" ͑ISE͒ method of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11] By contrast with the observation of "T"-shaped structures for Ar-C2H2 and Ar-CC>2, the linear configuration of He-C2H2 is the global minimum (according to an ab initio calculation12) and the C20 structure lies higher in energy, though a model potential suggested that the reverse is true. 12 The former result would suggest that the smaller helium atom is more sensitive to what (small) anisotropies there are in the acetylene potential than is the argon atom.…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular interactions between acetylene and rare gas atoms have been extensively investigated using high resolution spectroscopy, [3][4][5][6][7][8][9][10] scattering techniques, [11][12][13][14] and ab initio methods. 9,[15][16][17][18][19][20][21] The Ar-acetylene van der Waals dimer is the one most extensively studied. It was first studied by DeLeon and Muenter, using the molecular beam electric resonance technique.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the studies on Ar-acetylene, there are also a few ab initio intermolecular potentials reported for the He-acetylene system. Slee et al constructed a potential energy surface at the MP2 level, 16 which failed to explain the recorded infrared spectrum. 23 More recently, a SAPT potential energy surface for He-HCCH was constructed by Moszynski et al 18 It shows that acetylene behaves as an essentially free internal rotor.…”
Section: Introductionmentioning
confidence: 99%